Traditional children's games - Cintia Lyse Alves Nascimento; Eva Zatur; Fernanda Rocha Pereira (Universidade Federal de Santa Catarina, 2000)
Redeem a fascinating experience of the traditional game, creating and recreating the magic of play, the interaction, the exchange with the other ... in the formation of groups.